Does identification to species level provide sufficient evidence to confirm catheter-related fungemia caused by Candida albicans?. (October 2013) - Escribano, Pilar; Guinea, Jesús; Marcos-Zambrano, Laura; Recio, Sandra; Peláez, Teresa; Rodríguez-Créixems, Marta; Muñoz, Patricia; Bouza, Emilio
Abstract We retrospectively studied 22 patients with catheter-related candidemia caused by Candida albicans. Strains isolated simultaneously from blood and catheter tips were genotyped using six microsatellite markers. Matches between genotypes of isolates recovered from both sample sources were found in 20/22 (91%) patients. Consequently, identification of the same species from both the catheter tip and blood could be used to confirm catheter-related candidemia.